Phonon routing, modulation, and sensitive motion detection in piezo-optomechanical circuits - Balram, Krishna C.; Srinivasan, Kartik; Song, Jin Dong; Davanco, Marcelo (2016 CONFERENCE ON LASERS AND ELECTRO-OPTICS (CLEO), 2016)
We demonstrate an optomechanical circuit platform in GaAs in which optomechanical cavities are interfaced with interdigitated-transducers using phononic crystal waveguides. We use this platform to demonstrate phonon routing, acousto-optic and opto-acoustic modulation, and sensitive detection.